A dragon eating its own tail: public control of air pollution information in China. (9th November 2018) - Ravetti, Chiara; Swanson, Tim; Jin, Yana; Mu, Quan; Zhang, Shiqiu
Abstract: This paper analyses the implications of government control over public information about air pollution. First, we model the incentives for a local government with control over the media to affect popular perception concerning pollution. We argue that biased announcements can influence the inflows of labour force in a municipality beyond economic factors. Then, we examine some evidence on information misreporting in the context of Beijing, China. We show that official air pollution announcements diverge systematically from an alternative source of information, provided by the US Embassy. The results point at a manipulation of popular perception consistent with the motives indicated in our model. Furthermore, using an original household survey, we examine whether the distorted public signal affects agents' behaviour. We find that households that depend upon government-controlled media are significantly less responsive to pollution peaks.